AKIBAT HUKUM PEMBATALAN PERKAWINAN KARENA WALI NIKAH YANG TIDAK BERHAK TERHADAP KEDUDUKAN ANAK DAN HARTA BERSAMA MENURUT HUKUM ISLAM - Yulianti Maulidya; Imelda Martinelli (Jurnal Hukum Adigama, 2018)
Marriage is a physical and spiritual bond between man and woman who become husband and wife creating the happy and eternal family in the name of God Almighty. To conduct a marriage, the prospective groom and bride must meet marriage terms and conditions, or else the marriage itself may be cancelled. The cancellation of marriage is one way of breaking the  bond which requirements and principles are flawed. In the provisions of article 71 letter (e), the Islamic law compilation decrales that the marriage held without an authorized guardian will result on abolishment or be considered never exist. Neverthless, the cancelled marriage does not abolish the parental obligation of the children. The child remains legitimate and they are under their parents responsibility. Meanwhile, in the case of shared assets, in Islamic law, husband and wife can choose to use the method of Ash Sulh (negotiation),‘Urf (customary law), and the last option is Qadha (justice).